The Ecological Impact of the Covid-19 Pandemic Infodemic Discourse in Social Media: Ecolinguistic Perspectives - Khusnul Khotimah; Kisyani Laksono; Suhartono Suhartono; Udjang Pairin; Darni Darni (Universitas Muhammadiyah Sidoarjo, 2021)
Texts on social media often highlight the Covid-19 pandemic. The text influences the mindset and mode of the readers. The purpose of this study is to describe the potential ecological impacts of infodemics, both constructive and destructive for readers. Data sourced from social media (Facebook, Instagram, and Twitter). The method used in this research is a qualitative approach with descriptive methods. The results showed that the ecological impact of infodemic discourse, namely the constructive impact represented by the content, meaning or message can influence the mindset and attitudes of readers to participate in preserving the environment. Positive texts can change negative environmental ethics into positive ones. The destructive impact in the form of excessive use of text, and without clear sources, has an impact on the effects of distraction, mental health, panic buying, confirmation bias and echo chambers, and tends to refuse to protect oneself and heed health protocols, making it difficult to handle the outbreak. In addition, misinformation on health has an impact on exacerbating outbreaks of infectious diseases. Especially damaging advice as false information is crafted with no respect for accuracy and is often integrated with narratives framed by emotion or conspiracy. The text affects attitudes and mindsets so that it damages the environment.